Engineered circular RNA-based DLL3-targeted CAR-T therapy for small cell lung cancer - Jingsheng Cai; Zheng Liu; Shaoyi Chen; Jingwei Zhang; Haoran Li; Xun Wang; Feng Yang; Shaodong Wang; Xiao Li; Yun Li; Kezhong Chen; Jun Wang; et al. (Experimental Hematology & Oncology)
Abstract Purpose Circular RNA (circRNA) has emerged as a promising RNA therapeutic molecule due to its enhanced stability and prolonged protein expression compared to messenger RNA (mRNA). Using circRNA to construct transient Chimeric Antigen Receptor (CAR)-T cells can mitigate the limitations of conventional viral vector-based CAR-T approaches, such as complex process and long-term side effects. Methods The study first reconfirmed the advantageous properties of circRNA, focusing on its stability and protein expression efficiency. Electroporation conditions were then optimized for the efficient delivery of circRNA into human primary T cells. Subsequently, a circRNA encoding the anti-Delta-like Ligand 3 (DLL3) CAR was constructed, and CAR-T cells were generated via electroporation. The efficacy of circRNA-based CAR-T cells was compared to mRNA-based CAR-T cells in both in vitro and in vivo models, including subcutaneous and orthotopic small cell lung cancer (SCLC) mouse models. Results CircRNA-based CAR-T cells demonstrated superior efficacy against SCLC compared to mRNA-based CAR-T cells. In vitro experiments showed enhanced tumor-killing effects, while in vivo studies revealed complete elimination of human SCLC tumors in both subcutaneous and orthotopic mouse models. These results underscored the therapeutic advantages of circRNA in CAR-T cell therapy. Conclusions This study validated the feasibility of the circRNA-electroporation strategy in CAR-T cell therapy and offered a potentially effective approach for treating SCLC, highlighting the potential of circRNA-based technologies in advancing cell therapies. Graphic Abstract